Polymer reinforced expansive soil swelling inhibitor and method of making same

CN122978978APending Publication Date: 2026-10-27GUANGXI TRANSPORTATION SCI & TECH GRP CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202611189486.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-06
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

无机固化材料虽可提高强度,但用量较大,施工扬尘明显,且在干湿循环下易出现脆性开裂;单一聚合物虽具有一定胶结、增稠或保水作用,但通常难以同时兼顾抑制吸水膨胀、降低裂隙扩展、提高浸水承载性能和保持长期稳定性

Benefits of technology

[0025]与单一聚合物抑胀剂相比,本发明通过水溶性聚合物桥联组分、多价金属盐和疏水成膜组分的协同作用,在膨胀土颗粒之间产生桥联吸附、多价离子作用和疏水覆盖等复合作用,能够更有效地降低膨胀土的自由膨胀率、无荷载膨胀率和膨胀力。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122978978A_ABST
    Figure CN122978978A_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of soil conditioning, and discloses a polymer reinforced swelling soil expansion inhibitor and a preparation method thereof.The expansion inhibitor is composed of component A and component B.Component A includes lignin sulfonate, carboxymethyl cellulose salt, polyacrylic acid salt, polymer emulsion and silane hydrophobic component, and component B includes calcium salt, magnesium salt and dispersion stabilizer.When used, component A and component B are compounded with water and applied to swelling soil, which is beneficial to the generation of polymer bridging, polyvalent ion action and hydrophobic film forming among swelling soil particles, so as to reduce the swelling rate and swelling force, and improve the dry-wet cycle stability and roadbed bearing performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of soil conditioning technology, and in particular to a polymer-reinforced swelling inhibitor for expansive soil and its preparation method. Background Technology

[0002] Expansive soil is a special type of soil rich in hydrophilic clay minerals such as montmorillonite. It is characterized by swelling upon contact with water, shrinking upon loss of water, and being prone to cracking and strength reduction after wet-dry cycles. In the treatment of road subgrades, slopes, canals, and foundations, the volume deformation of expansive soil can easily cause pavement heave, slope cracking, and a decrease in bearing capacity. Therefore, swelling suppression and stabilization treatments are necessary.

[0003] Existing methods for treating expansive soil mainly include modifications using inorganic solidification materials such as lime, cement, and fly ash, as well as modifications using polymer materials such as polyacrylamide, polyvinyl alcohol, polyacrylate, and bio-adhesives. While inorganic solidification materials can improve strength, they require large quantities, generate significant dust during construction, and are prone to brittle cracking under wet-dry cycles. Although single polymers have certain cementing, thickening, or water-retaining effects, they are usually difficult to simultaneously inhibit water absorption and swelling, reduce crack propagation, improve water-bearing capacity, and maintain long-term stability.

[0004] Chinese patent CN119638276A discloses a method for improving expansive soil, its preparation, and its application. It uses a compound of biopolymer, wood ash, and plant matrix with expansive soil, improving soil properties through bonding, ion exchange, and reinforcement with plant fibers. However, this method primarily involves ecological solid-liquid admixture modification and does not address the formation of a hydrophobic film layer using polymer emulsions and hydrophobic silane components. Chinese patent CN121379597A discloses a composite modifier for expansive soil, which uses Ca... 2+ A core-shell structured particle is made from a cation exchange resin and cationic polyacrylamide to achieve ion exchange and particle agglomeration, but no hydrophobic film-forming component is introduced, and it is not a two-component liquid swelling inhibitor suitable for on-site dilution, spraying, or mixing. Chinese patent CN121470848A discloses an improved expansive soil based on the synergistic effect of marble waste powder and xanthan gum, which mainly relies on solid waste powder filling and xanthan gum binding, and does not involve polymer ion crosslinking induced by polyvalent metal salts or hydrophobic film-forming structure.

[0005] Therefore, existing technologies still cannot effectively address the problems of water absorption, swelling, and cyclic deterioration of expansive soils from three levels: polymer bridging, ionic crosslinking, and hydrophobic water blocking. There is an urgent need to provide an expansion inhibitor that can form a stable bridging structure between expansive soil particles and simultaneously reduce the ability of water to enter the soil pores and clay mineral layers. Summary of the Invention

[0006] In view of the above-mentioned deficiencies of the prior art, the technical problem to be solved by the present invention is to provide a polymer-reinforced expansive soil swelling inhibitor and its preparation method, which can synergistically reduce the water absorption and swelling, dry-wet cycle cracking and water immersion strength decay of expansive soil.

[0007] To achieve the above objectives, the present invention provides a polymer-reinforced expansive soil swelling inhibitor, the swelling inhibitor comprising component A and component B; component A comprises a water-soluble polymer bridging component, a polymer emulsion, a silane hydrophobic component, an antifoaming agent, and a preservative; component B comprises a polyvalent metal salt and a dispersing stabilizer.

[0008] Preferably, the water-soluble polymer bridging component comprises at least two of lignin sulfonate, carboxymethyl cellulose salt, and polyacrylate. More preferably, the water-soluble polymer bridging component comprises sodium lignin sulfonate, sodium carboxymethyl cellulose, and low molecular weight sodium polyacrylate.

[0009] Preferably, the polymer emulsion is one or more selected from ethylene-vinyl acetate copolymer emulsion, acrylate emulsion, styrene-acrylic emulsion, and silicone-acrylic emulsion. More preferably, the polymer emulsion is an ethylene-vinyl acetate copolymer emulsion.

[0010] Preferably, the silane hydrophobic component is an alkyltrialkoxysilane, a silane emulsion, or a combination thereof. More preferably, the silane hydrophobic component is an octyltriethoxysilane emulsion, and the octyltriethoxysilane content is 40 wt%.

[0011] Preferably, the polyvalent metal salt includes a calcium salt and a magnesium salt; the calcium salt is one or more of calcium acetate, calcium chloride, and calcium nitrate, and the magnesium salt is one or more of magnesium chloride, magnesium sulfate, and magnesium acetate. More preferably, the polyvalent metal salt includes calcium acetate monohydrate and magnesium chloride hexahydrate.

[0012] Preferably, the dispersant stabilizer is one or more selected from sodium gluconate, sodium citrate, and sodium tartrate. More preferably, the dispersant stabilizer is sodium gluconate.

[0013] Preferably, the mass ratio of component A to component B is 3-6:1. More preferably, the mass ratio of component A to component B is 4:1.

[0014] Preferably, component A comprises, by weight, 40-70 parts deionized water, 8-18 parts lignin sulfonate, 0.5-5 parts carboxymethyl cellulose salt, 1-8 parts polyacrylate, 8-25 parts polymer emulsion, 0.5-5 parts silane hydrophobic component, 0.05-0.5 parts defoamer, and 0.02-0.3 parts preservative.

[0015] Preferably, component B comprises, by mass, 40-70 parts of deionized water, 20-40 parts of calcium salt, 8-20 parts of magnesium salt, and 1-5 parts of dispersant stabilizer.

[0016] The present invention also provides a method for preparing the above-mentioned polymer-reinforced expansive soil swelling inhibitor, comprising the following steps:

[0017] 1) After heating deionized water, add water-soluble polymer bridging components, stir to dissolve, and obtain polymer bridging solution;

[0018] 2) Add polymer emulsion, silane hydrophobic component, defoamer and preservative to the polymer bridging liquid obtained in step 1), stir evenly to obtain component A;

[0019] 3) Add the polyvalent metal salt and dispersant stabilizer to deionized water, stir to dissolve, and obtain component B;

[0020] 4) Filter and seal components A and B separately to obtain a polymer-reinforced expansive soil swelling inhibitor composed of components A and B.

[0021] Preferably, during use, component A, component B, and water are mixed in a mass ratio of 3-6:1:8-15, and stirred evenly to obtain a construction-grade swelling-suppressing treatment solution; the construction-grade swelling-suppressing treatment solution is added to the expansive soil and mixed evenly, followed by compaction and curing. Preferably, the amount of the construction-grade swelling-suppressing treatment solution added is 5-15% of the dry mass of the expansive soil.

[0022] More preferably, the mass ratio of component A, component B and water is 4:1:10.

[0023] The technical concept of this invention lies in using water-soluble polymers containing carboxyl, hydroxyl, and sulfonic acid groups to enhance their adsorption on the surface of expansive soil particles and the interparticle bridging effect; utilizing the complexation, ionic interaction, or cation exchange between calcium and magnesium ions and polymer segments and active sites on the surface of soil particles to improve the structural stability between particles; and utilizing polymer emulsions and silane hydrophobic components to improve the wettability of soil particle surfaces and form a hydrophobic coating, thereby synergistically reducing the expansion caused by water entering soil pores and clay mineral layers, and improving the stability of the soil under wet-dry cycles and immersion conditions.

[0024] The beneficial effects of this invention are:

[0025] Compared with single polymer swelling inhibitors, this invention utilizes the synergistic effect of water-soluble polymer bridging components, multivalent metal salts, and hydrophobic film-forming components to generate a complex effect of bridging adsorption, multivalent ion interaction, and hydrophobic covering between expansive soil particles, which can more effectively reduce the free swelling rate, unloaded swelling rate, and swelling force of expansive soil.

[0026] Compared with solutions that only use hydrophobic emulsions or inorganic salts, this invention can reduce the water absorption rate through the hydrophobic film layer and improve the interparticle bonding strength through ionic crosslinking and polymer networks, thereby improving the strength retention rate, water immersion CBR and bearing stability of expansive soil under immersion conditions.

[0027] Compared with single-packaged mixed swelling inhibitors, this invention uses separate packaging of components A and B, and recombination before use, to avoid premature cross-linking or flocculation of polymers and polyvalent metal ions during storage, ensuring uniform dispersion during construction, and enabling ionic cross-linking and hydrophobic film formation to occur simultaneously inside the expansive soil, thereby improving the swelling retention rate and crack resistance after wet-dry cycles. Attached Figure Description

[0028] Figure 1 These are comparative images showing the development of cracks in expansive soil after 10 wet-dry cycles. Figure 1 Group A is the blank group. Figure 1 B is the treatment group of Example 1.

[0029] Figure 2 These are comparative images showing the disintegration states of expansive soil after immersion and settling in water. Figure 2 Group A is the blank group. Figure 2 B is the treatment group of Example 1. Detailed Implementation

[0030] The parameters and sources of some raw materials in the examples are as follows:

[0031] Sodium lignosulfonate, CAS No.: 8061-51-6, is a brownish-yellow to brownish-brown powder with a lignosulfonate content of not less than 92 wt%, a moisture content of not more than 7 wt%, and a pH value of 7.0-10.0.

[0032] Sodium carboxymethyl cellulose, CAS No.: 9004-32-4, degree of substitution: 0.70-0.90, viscosity of 1wt% aqueous solution: 800-1200 mPa·s.

[0033] Low molecular weight sodium polyacrylate, CAS No.: 9003-04-7, weight average molecular weight is 3000-5000.

[0034] Ethylene-vinyl acetate copolymer emulsion, model: CW40-907J, solid content ≥54.5wt%, viscosity (25℃) 600-1200mPa·s, minimum film-forming temperature not higher than 1℃, sourced from Chongqing Chuanwei Chemical Co., Ltd., China Petrochemical Corporation.

[0035] Octyltriethoxysilane emulsion is prepared by high-speed shear emulsification of octyltriethoxysilane (CAS No.: 2943-75-1), fatty alcohol polyoxyethylene ether AEO-7, and deionized water; wherein, the mass content of octyltriethoxysilane is 40wt%, the mass content of fatty alcohol polyoxyethylene ether is 3wt%, and the balance is deionized water. It is a milky white liquid with a pH value of 6.0-8.0.

[0036] Silicone defoamer, model number: BYK-024, is sourced from BYK, Germany.

[0037] Isothiazolinone preservative, model: Kathon CG, the main active ingredient is a compound of 5-chloro-2-methyl-4-isothiazolin-3-one and 2-methyl-4-isothiazolin-3-one, with an active ingredient content of 1.5 wt%, sourced from Dow Chemical.

[0038] The expansive soil was collected from a roadbed construction site in Xiangyang City, Hubei Province. After being air-dried, it was crushed and passed through a 2mm sieve. Its liquid limit was 61.8%, plastic limit was 28.6%, plasticity index was 33.2, and free swelling rate was 78.5%, which means it belongs to highly expansive clay.

[0039] Example 1

[0040] A method for preparing a polymer-reinforced swelling inhibitor for expansive soil includes the following steps:

[0041] 1) Preparation of polymer bridging solution: Add 45.20 kg of deionized water to a reactor equipped with a stirrer, start stirring at 400 r / min, heat to 45℃, and then add 12.00 kg of sodium lignosulfonate, 2.00 kg of sodium carboxymethyl cellulose and 3.00 kg of low molecular weight sodium polyacrylate in sequence. Continue stirring for 50 min to dissolve the sodium lignosulfonate, sodium carboxymethyl cellulose and low molecular weight sodium polyacrylate to obtain the polymer bridging solution;

[0042] 2) Preparation of hydrophobic film-forming mixture: Cool the polymer bridging liquid obtained in step 1) to 35℃, add 15.00 kg of ethylene-vinyl acetate copolymer emulsion while stirring at 500 r / min, stir for 20 min, then add 2.50 kg of octyltriethoxysilane emulsion, 0.20 kg of organosilicon defoamer and 0.10 kg of isothiazolinone preservative, and continue stirring for 40 min to obtain component A;

[0043] 3) Preparation of ion crosslinking solution: Add 11.40 kg of deionized water to another reactor, start stirring at 350 r / min, add 5.50 kg of calcium acetate monohydrate, 2.50 kg of magnesium chloride hexahydrate and 0.60 kg of sodium gluconate at 25℃, stir for 35 min to dissolve calcium acetate monohydrate, magnesium chloride hexahydrate and sodium gluconate to obtain component B;

[0044] 4) Packaging: Filter the A component obtained in step 2) and the B component obtained in step 3) respectively with a 100-mesh sieve; after filtration, seal the A component and the B component separately to obtain the polymer-reinforced expansive soil swelling inhibitor composed of the A component and the B component.

[0045] Instructions for use: Mix component A, component B, and water at a mass ratio of 4:1:10 and stir for 10 minutes at a stirring speed of 300 r / min to obtain a construction-grade swelling-suppressing treatment solution. Add the construction-grade swelling-suppressing treatment solution to the expansive soil and mix thoroughly. Then compact and cure. This process facilitates the adsorption and bridging of polymer segments between expansive soil particles, promotes the complexation or ionic interaction of calcium and magnesium ions with polymer segments and active sites on the surface of soil particles, and facilitates the formation of a hydrophobic coating layer on the surface of soil particles by EVA emulsion and silane hydrophobic components, thereby obtaining treated expansive soil. The amount of swelling-suppressing treatment solution used is 10 wt% of the mass of the expansive soil.

[0046] Comparative Example 1

[0047] A method for preparing a polymer-reinforced swelling inhibitor for expansive soil, differing from Example 1 in that it does not include ethylene-vinyl acetate copolymer emulsion and octyltriethoxysilane emulsion, specifically comprising the following steps:

[0048] 1) Preparation of polymer bridging solution: Add 62.70 kg of deionized water to a reactor equipped with a stirrer, start stirring at 400 r / min, heat to 45℃, and then add 12.00 kg of sodium lignosulfonate, 2.00 kg of sodium carboxymethyl cellulose and 3.00 kg of low molecular weight sodium polyacrylate in sequence. Continue stirring for 50 min to dissolve the sodium lignosulfonate, sodium carboxymethyl cellulose and low molecular weight sodium polyacrylate to obtain the polymer bridging solution;

[0049] 2) Preparation of component A: Cool the polymer bridging liquid obtained in step 1) to 35°C, add 0.20 kg of organosilicon defoamer and 0.10 kg of isothiazolinone preservative while stirring at 500 r / min, and continue stirring for 40 min to obtain component A;

[0050] 3) Preparation of ion crosslinking solution: Add 11.40 kg of deionized water to another reactor, start stirring at 350 r / min, add 5.50 kg of calcium acetate monohydrate, 2.50 kg of magnesium chloride hexahydrate and 0.60 kg of sodium gluconate at 25℃, stir for 35 min to dissolve calcium acetate monohydrate, magnesium chloride hexahydrate and sodium gluconate to obtain component B;

[0051] 4) Packaging: Filter the A component obtained in step 2) and the B component obtained in step 3) respectively with a 100-mesh sieve; after filtration, seal the A component and the B component separately to obtain the polymer-reinforced expansive soil swelling inhibitor composed of the A component and the B component.

[0052] Instructions for use: Mix component A, component B and water at a mass ratio of 4:1:10 and stir for 10 minutes at a stirring speed of 300 r / min to obtain a construction swelling suppression treatment liquid; add the construction swelling suppression treatment liquid to the expansive soil and mix evenly, then compact and cure to obtain the treated expansive soil; the amount of swelling suppression treatment liquid used is 10 wt% of the mass of the expansive soil.

[0053] Comparative Example 2

[0054] A method for preparing a polymer-reinforced swelling inhibitor for expansive soil, differing from Example 1 in that calcium acetate monohydrate, magnesium chloride hexahydrate, and sodium gluconate are not added, specifically including the following steps:

[0055] 1) Preparation of polymer bridging solution: Add 45.20 kg of deionized water to a reactor equipped with a stirrer, start stirring at 400 r / min, heat to 45℃, and then add 12.00 kg of sodium lignosulfonate, 2.00 kg of sodium carboxymethyl cellulose and 3.00 kg of low molecular weight sodium polyacrylate in sequence. Continue stirring for 50 min to dissolve the sodium lignosulfonate, sodium carboxymethyl cellulose and low molecular weight sodium polyacrylate to obtain the polymer bridging solution;

[0056] 2) Preparation of hydrophobic film-forming mixture: Cool the polymer bridging liquid obtained in step 1) to 35℃, add 15.00 kg of ethylene-vinyl acetate copolymer emulsion while stirring at 500 r / min, stir for 20 min, then add 2.50 kg of octyltriethoxysilane emulsion, 0.20 kg of organosilicon defoamer and 0.10 kg of isothiazolinone preservative, and continue stirring for 40 min to obtain component A;

[0057] 3) Preparation of component B: Add 20.00 kg of deionized water to another reactor and stir until homogeneous to obtain component B;

[0058] 4) Packaging: Filter the A component obtained in step 2) and the B component obtained in step 3) respectively with a 100-mesh sieve; after filtration, seal the A component and the B component separately to obtain the polymer-reinforced expansive soil swelling inhibitor composed of the A component and the B component.

[0059] Instructions for use: Mix component A, component B and water at a mass ratio of 4:1:10 and stir for 10 minutes at a stirring speed of 300 r / min to obtain a construction swelling suppression treatment liquid; add the construction swelling suppression treatment liquid to the expansive soil and mix evenly, then compact and cure to obtain the treated expansive soil; the amount of swelling suppression treatment liquid used is 10 wt% of the mass of the expansive soil.

[0060] Comparative Example 3

[0061] A method for preparing a polymer-reinforced expansive soil swelling inhibitor, differing from Example 1 in that sodium lignosulfonate, sodium carboxymethyl cellulose, and low molecular weight sodium polyacrylate are not added, and specifically includes the following steps:

[0062] 1) Preparation of hydrophobic film-forming mixture: Add 62.20 kg of deionized water to a reactor equipped with a stirrer, start stirring at 400 r / min, heat to 35℃, add 15.00 kg of ethylene-vinyl acetate copolymer emulsion, stir for 20 min, then add 2.50 kg of octyltriethoxysilane emulsion, 0.20 kg of organosilicon defoamer and 0.10 kg of isothiazolinone preservative, and continue stirring for 40 min to obtain component A;

[0063] 2) Preparation of ion crosslinking solution: Add 11.40 kg of deionized water to another reactor, start stirring at 350 r / min, add 5.50 kg of calcium acetate monohydrate, 2.50 kg of magnesium chloride hexahydrate and 0.60 kg of sodium gluconate at 25℃, stir for 35 min to dissolve calcium acetate monohydrate, magnesium chloride hexahydrate and sodium gluconate to obtain component B;

[0064] 3) Packaging: Filter the A component obtained in step 1) and the B component obtained in step 2) respectively with a 100-mesh sieve; after filtration, seal the A component and the B component separately to obtain the polymer-reinforced expansive soil swelling inhibitor composed of the A component and the B component.

[0065] Instructions for use: Mix component A, component B and water at a mass ratio of 4:1:10 and stir for 10 minutes at a stirring speed of 300 r / min to obtain a construction swelling suppression treatment liquid; add the construction swelling suppression treatment liquid to the expansive soil and mix evenly, then compact and cure to obtain the treated expansive soil; the amount of swelling suppression treatment liquid used is 10 wt% of the mass of the expansive soil.

[0066] Comparative Example 4

[0067] A method for preparing a polymer-reinforced expansive soil swelling inhibitor differs from Example 1 in that the composition of each raw material is the same as in Example 1, but instead of using the separate packaging method for components A and B, the polymer bridging component, hydrophobic film-forming component, and ionic crosslinking component are prepared into a single-packaged mixture. The specific steps include the following:

[0068] 1) Preparation of polymer bridging solution: Add 56.60 kg of deionized water to a reactor equipped with a stirrer, start stirring at 400 r / min, heat to 45℃, and then add 12.00 kg of sodium lignosulfonate, 2.00 kg of sodium carboxymethyl cellulose and 3.00 kg of low molecular weight sodium polyacrylate in sequence. Continue stirring for 50 min to dissolve the sodium lignosulfonate, sodium carboxymethyl cellulose and low molecular weight sodium polyacrylate to obtain the polymer bridging solution;

[0069] 2) Preparation of hydrophobic film-forming mixture: Cool the polymer bridging liquid obtained in step 1) to 35℃, add 15.00 kg of ethylene-vinyl acetate copolymer emulsion while stirring at 500 r / min, stir for 20 min, then add 2.50 kg of octyltriethoxysilane emulsion, 0.20 kg of organosilicon defoamer and 0.10 kg of isothiazolinone preservative, and continue stirring for 40 min to obtain the hydrophobic film-forming mixture;

[0070] 3) Adding ionic crosslinking components: Under the conditions of stirring speed of 350 r / min and temperature of 25℃, add 5.50 kg of calcium acetate monohydrate, 2.50 kg of magnesium chloride hexahydrate and 0.60 kg of sodium gluconate to the hydrophobic film-forming mixture obtained in step 2), stir for 35 min, and obtain a single-package mixture;

[0071] 4) Packaging: The single-packaged mixture obtained in step 3) is filtered through a 100-mesh sieve and then sealed to obtain a single-packaged polymer-reinforced expansive soil swelling inhibitor.

[0072] Instructions for use: Mix the single-packaged polymer-reinforced expansive soil swelling inhibitor with water at a mass ratio of 1:2, and stir for 10 minutes at a stirring speed of 300 r / min to obtain a construction swelling inhibitor solution; add the construction swelling inhibitor solution to the expansive soil and mix evenly, then compact and cure to obtain the treated expansive soil; the amount of swelling inhibitor solution used is 10 wt% of the mass of the expansive soil.

[0073] Comparative Example 5

[0074] A method for preparing an expansive soil swelling inhibitor differs from Example 1 in that only low molecular weight sodium polyacrylate is used as a single polymer swelling inhibitor component, and the amount of low molecular weight sodium polyacrylate used is the same as the total amount of sodium lignosulfonate, sodium carboxymethyl cellulose, and low molecular weight sodium polyacrylate used in Example 1. The method specifically includes the following steps:

[0075] 1) Preparation of polymer solution: Add 82.70 kg of deionized water to a reactor equipped with a stirrer, turn on the stirrer at a speed of 400 r / min, heat to 45℃, add 17.00 kg of low molecular weight sodium polyacrylate in batches, and continue stirring for 50 min to dissolve the low molecular weight sodium polyacrylate and obtain the polymer solution.

[0076] 2) Adding additives: Cool the polymer solution obtained in step 1) to 35°C, add 0.20 kg of organosilicon defoamer and 0.10 kg of isothiazolinone preservative, and continue stirring for 40 min; after filtering with a 100-mesh sieve, seal and package to obtain the swelling inhibitor of expansive soil.

[0077] Instructions for use: Mix the swelling inhibitor and water at a mass ratio of 1:2 and stir for 10 minutes at a stirring speed of 300 r / min to obtain the swelling inhibitor treatment liquid for construction; add the swelling inhibitor treatment liquid for construction to the swelling soil and mix evenly, then compact and cure to obtain the treated swelling soil; the amount of swelling inhibitor treatment liquid used is 10 wt% of the mass of the swelling soil.

[0078] Test sample preparation

[0079] The same batch of expansive soil was used as the test soil sample, air-dried, and then crushed for later use. Samples were prepared separately according to different test items: soil samples for the free swelling rate test were air-dried, gently crushed, and passed through a 0.5 mm sieve; soil samples for the unloaded swelling rate, swelling force, wet-dry cycle stability, unconfined compressive strength, and CBR tests were air-dried, crushed, and passed through a 2 mm sieve. The expansive soil had a liquid limit of 61.8%, a plastic limit of 28.6%, a plasticity index of 33.2, and a free swelling rate of 78.5%, classifying it as a highly expansive clay.

[0080] According to the compaction test in T 0131-2019 of JTG 3430-2020 "Specifications for Geotechnical Testing of Highways", the optimum moisture content of the expansive soil is 21.6%, and the maximum dry density is 1.67 g / cm³. 3 .

[0081] Pre-test storage treatment: Components A and B obtained in Examples 1, 1 to 3 were sealed and stored at 40°C for 14 days. After storage, components A and B were mixed with water according to their respective usage methods to prepare a construction-grade swelling inhibitor. The single-package polymer-reinforced expansive soil swelling inhibitor obtained in Comparative Example 4 was sealed and stored at 40°C for 14 days. After storage, it was diluted with water according to its usage method to prepare a construction-grade swelling inhibitor. The single polymer-type control swelling inhibitor obtained in Comparative Example 5 was sealed and stored at 40°C for 14 days. After storage, it was diluted with water according to its usage method to prepare a construction-grade swelling inhibitor. The test results in Tables 1 to 4 are the test results of the samples after the above storage.

[0082] In Examples 1 and 5, construction-grade swelling-suppressing treatment solutions were prepared according to their respective methods and added to the expansive soil at a ratio of 10.0% of the dry soil mass. The moisture content of the construction-grade swelling-suppressing treatment solution was included in the sample molding moisture content. All samples were prepared with a target moisture content of 21.6% and a target compaction degree of 95%, i.e., a target dry density of 1.59 g / cm³. 3 During sample preparation, the actual moisture content of the air-dried soil sample and the water mass fraction of the swelling-suppressing treatment solution were first determined. Then, the amount of water to be added was calculated based on the target moisture content. After the swelling-suppressing treatment solution, added water, and expansive soil were thoroughly mixed, the mixture was sealed and allowed to stand for 12 hours to allow for uniform distribution of moisture and swelling-suppressing components. Compacted samples were then prepared according to the corresponding test methods. The blank group did not contain any swelling inhibitors; only deionized water of the same mass as the swelling-suppressing treatment solution was added, and samples were prepared according to the same target moisture content and compaction degree. All samples were cured for 7 days at a temperature of 20±2℃ and a relative humidity of over 95% before testing.

[0083] Test Example 1

[0084] Expansion performance test

[0085] Free swelling rate, unloaded swelling rate, and swelling force were tested according to the free swelling rate test, swelling rate test, and swelling force test in GB / T 50123-2019 "Standard for Geotechnical Testing Methods". The free swelling rate test used unstructured soil samples that had been treated, cured, air-dried, lightly rolled, and sieved through a 0.5 mm sieve. The unloaded swelling rate and swelling force tests used compacted samples prepared at optimum moisture content and 95% compaction degree. Three parallel samples were set for each group, and the average value was taken as the test result. The lower the free swelling rate, the weaker the tendency of the soil sample to expand in volume after contact with water; the lower the unloaded swelling rate, the better the volume stability of the compacted soil sample after absorbing water; the lower the swelling force, the smaller the bulging effect of the soil's water absorption on the engineering structure.

[0086] Table 1. Test results of expansion performance of different treatment groups

[0087]

[0088] As shown in Table 1, the free swelling rate, unloaded swelling rate, and swelling force of the expansive soil treated in Example 1 were significantly lower than those of the blank group and the comparative examples. Specifically, the free swelling rate of Example 1 decreased from 78.5% in the blank group to 24.6%, and the swelling force decreased from 155 kPa to 38 kPa, indicating that Example 1 can effectively inhibit the volume expansion of expansive soil after it comes into contact with water.

[0089] Comparative Example 1, which did not contain ethylene-vinyl acetate copolymer emulsion and octyltriethoxysilane emulsion, retained the polymer bridging component and ionic crosslinking component, but its free expansion rate, unloaded expansion rate and expansion force were all higher than those of Example 1, indicating that the polymer emulsion and silane hydrophobic component help to further improve the expansion inhibition effect.

[0090] Comparative Example 2, which did not contain calcium salts, magnesium salts, or dispersant stabilizers in the ionic crosslinking solution, exhibited significantly higher swelling force and unloaded swelling rate than Example 1, indicating that ionic crosslinking plays an important role in improving the structural stability between particles.

[0091] Comparative Example 3, which did not include polymer bridging components, showed a further decrease in swelling suppression effect, indicating that simple hydrophobic film formation and ionic salt treatment are insufficient to form a stable bridging network between expansive soil particles.

[0092] Comparative Example 4 used the same raw material composition as Example 1 and was also stored in a sealed container at 40°C for 14 days before use. The difference between Comparative Example 4 and Example 1 is that Comparative Example 4 prepared the polymer bridging component, hydrophobic film-forming component, and ionic crosslinking component into a single-package mixture, while Example 1 used components A and B separately for storage and recombining before use. As shown in Table 1, the free expansion rate, unloaded expansion rate, and expansion force of Comparative Example 4 were all higher than those of Example 1, indicating that under the same accelerated storage conditions, the two-component packaging method is beneficial for maintaining the construction dispersion and expansion suppression effect after storage.

[0093] Comparative Example 5 used low molecular weight sodium polyacrylate with the same total amount of water-soluble polymer bridging components as in Example 1 as a single polymer anti-swelling component. Its free expansion rate, unloaded expansion rate, and expansion force were all lower than those of the blank group, indicating that low molecular weight sodium polyacrylate itself has a certain anti-swelling effect; however, its various indicators were still significantly weaker than those of Example 1, indicating that it is difficult to achieve composite bridging, ionic crosslinking, and hydrophobic water-blocking effects by relying solely on sodium polyacrylate.

[0094] Test Example 2

[0095] Dry-wet cycle stability and crack suppression performance test

[0096] Compacted soil samples cured for 7 days were subjected to wet-dry cycle tests. One wet-dry cycle consisted of a water absorption phase and a drying phase: the water absorption phase involved placing the bottom of the sample in water for capillary absorption for 24 hours, and the drying phase involved placing the sample in a 50℃ forced-air drying oven until the mass change rate was less than 0.1%. Ten wet-dry cycles were repeated. After completing the specified number of cycles, the samples used for the free swelling rate test were air-dried, lightly rolled, and sieved through a 0.5mm sieve. The free swelling rate after the wet-dry cycle was then determined according to the free swelling rate test in GB / T 50123-2019 "Standard for Geotechnical Testing Methods". Simultaneously, the surface of another set of compacted samples after completing the wet-dry cycle was photographed, and image analysis software was used to statistically analyze the crack area ratio and maximum crack width.

[0097] Table 2. Stability test results after wet and dry cycles for different treatment groups

[0098]

[0099] Note: Increase in free expansion rate = Free expansion rate after 10 wet-dry cycles - Initial free expansion rate.

[0100] As shown in Table 2, after 10 wet-dry cycles, the free swelling rate of the control group increased from 78.5% to 87.2%, and the crack area ratio reached 18.6%, indicating that the expansive soil underwent significant structural deterioration during repeated water absorption and loss. In Example 1, after 10 wet-dry cycles, the free swelling rate was 27.8%, the increase in free swelling rate was only 3.2%, the crack area ratio was only 3.2%, and the maximum crack width was only 0.58 mm, demonstrating good long-term swelling suppression and crack resistance.

[0101] Comparative Example 1, lacking ethylene-vinyl acetate copolymer emulsion and octyltriethoxysilane emulsion, showed a free swelling rate of 42.9% after 10 wet-dry cycles, with an increase of 8.4% and a crack area ratio of 7.8%, indicating that the hydrophobic film-forming component helps reduce structural degradation caused by repeated water entry into soil pores during wet-dry cycles. Comparative Example 2, lacking calcium acetate monohydrate, magnesium chloride hexahydrate, and sodium gluconate, showed a free swelling rate of 55.6% after 10 wet-dry cycles, with an increase of 12.8%, indicating that component B, containing calcium and magnesium salts and a dispersant stabilizer, helps improve structural stability under cyclic water absorption conditions. Comparative Example 3, lacking a water-soluble polymer bridging component, showed a free swelling rate of 65.7% after 10 wet-dry cycles, with an increase of 14.5% and a crack area ratio of 13.7%, with a maximum crack width of 2.31 mm, indicating that the water-soluble polymer bridging component helps improve interparticle bonding and crack resistance. Although Comparative Example 4 used the same raw material composition as Example 1 and was also stored in a sealed container at 40°C for 14 days before use, it was a single-packaged mixture. After 10 wet-dry cycles, its free expansion rate was 48.6%, the increase in free expansion rate was 10.7%, and the crack area ratio was 9.4%, indicating that its wet-dry cycle stability after single-package storage was weaker than that of Example 1. Comparative Example 5 used a single low-molecular-weight sodium polyacrylate with an equal total polymer content. After 10 wet-dry cycles, its free expansion rate was 59.2%, the increase in free expansion rate was 12.4%, and the crack area ratio was 12.4%, indicating that it is difficult to obtain comparable cycle stability and crack resistance as Example 1 by relying solely on sodium polyacrylate. The above results show that Example 1, by using a two-component (A and B) packaging method and pre-use compounding, allows the water-soluble polymer bridging component, the calcium-magnesium salt-containing component B, and the hydrophobic film-forming component to work together in the soil, which can reduce the increase in free expansion rate after wet-dry cycles, and reduce the crack area ratio and maximum crack width, thereby improving wet-dry cycle stability and crack resistance.

[0102] The surface crack morphology of the sample after wet-dry cycling is as follows Figure 1 As shown. By Figure 1 It can be seen that after 10 dry and wet cycles, obvious cracks appeared on the surface of the blank group, and the degree of crack connectivity was relatively high; the surface cracks of the treatment group of Example 1 were significantly reduced, and the integrity of the sample was better, which is consistent with the results in Table 2 of Example 1, which showed lower crack area ratio and maximum crack width.

[0103] Test Example 3

[0104] Strength and subgrade bearing capacity test

[0105] Unconfined compressive strength was tested according to the unconfined compressive strength test in GB / T 50123-2019 "Standard for Geotechnical Testing Methods". CBR was tested according to the bearing ratio test in JTG 3430-2020 "Specifications for Highway Geotechnical Testing". All samples were prepared according to the aforementioned sample preparation method, i.e., with a target moisture content of 21.6% and a bearing ratio of 1.59 g / cm³. 3 Compacted specimens were prepared to achieve the target dry density and cured for 7 days at a temperature of 20±2℃ and a relative humidity of over 95% before testing. In the immersion CBR test, the specimens were immersed in water for 96 hours. Three parallel specimens were set up in each group, and the average value was taken as the test result. The strength retention rate was the ratio of the unconfined compressive strength of the specimen after 5 wet-dry cycles to the unconfined compressive strength of the uncycled specimen.

[0106] Table 3. Test results of strength and load-bearing capacity of different treatment groups

[0107]

[0108] As shown in Table 3, the unconfined compressive strength of the expansive soil treated in Example 1 reached 445 kPa, which was significantly higher than that of the blank group and the comparative examples; the water immersion CBR reached 9.6%, and the water immersion swelling was only 1.3%, indicating that Example 1 can not only inhibit swelling, but also improve the bearing capacity of expansive soil under water immersion conditions.

[0109] Comparative Example 1 lacked hydrophobic film-forming components, resulting in lower strength retention and CBR after immersion compared to Example 1, indicating that the hydrophobic film-forming layer can improve soil water stability. Comparative Example 2 lacked calcium and magnesium salts and dispersing stabilizers in the ionic crosslinking liquid, leading to insufficient interparticle bonding strength and a decrease in unconfined compressive strength and CBR. Comparative Example 3 lacked polymer bridging components, resulting in a lack of a continuous cementing network between soil particles and limited strength improvement. Comparative Example 4, under the same accelerated storage conditions, showed lower unconfined compressive strength, strength retention, and immersion CBR than Example 1, suggesting that single-package mixed storage may affect the dispersion and uniformity of the swelling inhibitor in the soil, thereby weakening the immersion bearing capacity. Although Comparative Example 5 increased the amount of single low molecular weight sodium polyacrylate, it still showed significantly lower unconfined compressive strength, strength retention rate, and water immersion CBR than Example 1 due to the lack of the composite bridging structure formed by sodium lignosulfonate and sodium carboxymethyl cellulose, as well as the lack of calcium and magnesium ion crosslinking and EVA / silane hydrophobic film-forming effect. This indicates that the improved load-bearing performance of Example 1 was not solely due to the increased amount of sodium polyacrylate. The above results demonstrate that Example 1 can improve strength and water immersion load-bearing performance while reducing swelling, exhibiting better applicability for roadbed treatment.

[0110] Test Example 4

[0111] Characterization of hydrophobicity and clay mineral interlayer spacing

[0112] The contact angle was measured using the seated drop method. Compacted samples of the treated expansive soil from each group were prepared and cured for 7 days. 5 μL of deionized water was then dropped onto the surface, and the static contact angle at 5 seconds was recorded using a contact angle meter. Five points were tested for each group, and the average value was taken. X-ray diffraction was used to observe the changes in the interlayer spacing of clay minerals in the expansive soil before and after treatment. The scanning range was 2θ = 3°–15°, and the scanning rate was 2° / min.

[0113] Table 4. Test results of hydrophobicity and clay mineral interlayer spacing in different treatment groups

[0114]

[0115] Table 4 shows that the static contact angle of the expansive soil treated in Example 1 reached 82°, significantly higher than that of the blank group and the comparative examples, indicating a reduction in surface wettability after treatment. Considering the addition of ethylene-vinyl acetate copolymer emulsion and octyltriethoxysilane emulsion in Example 1, it can be inferred that these components facilitate the formation of a hydrophobic coating or film-like structure on the soil particle surface. The interlayer spacing of clay minerals (d001) after 24 hours of immersion in water in Example 1 was 1.51 nm, lower than that of the blank group and the comparative examples, indicating a reduction in the degree of hydration and swelling between clay mineral layers after treatment. This result may be related to the interaction of polyvalent metal ions, polymer adsorption, and hydrophobic water-blocking effects.

[0116] Test Example 5

[0117] Observation of disintegration state in water

[0118] To further observe the structural stability of the expansive soil treated in Example 1 under immersion conditions, compacted samples from the blank group and the Example 1 treated group were used for water disintegration observation. The samples were prepared according to the aforementioned test sample preparation method, i.e., with a target moisture content of 21.6% and a density of 1.59 g / cm³. 3 Compacted samples were prepared to achieve the target dry density and then tested after curing at a temperature of 20±2℃ and a relative humidity of over 95% for 7 days.

[0119] During testing, the cured and compacted sample was slowly placed into a 500mL beaker containing 400mL of deionized water, ensuring complete immersion. No stirring was performed during the test. After standing for 30 minutes, the softening, disintegration, and turbidity of the sample in the water were observed and recorded by photograph. A comparison of the disintegration states in water between the blank group and the treatment group in Example 1 is provided. Figure 2 As shown.

[0120] Depend on Figure 2It is evident that the blank group samples disintegrated significantly after immersion in water, and the water became turbid, indicating that the untreated expansive soil had poor structural stability under immersion conditions. The treatment group in Example 1 maintained a better overall shape after immersion, and the turbidity of the water was significantly reduced, indicating that Example 1 can improve the structural stability and anti-disintegration performance of expansive soil under immersion conditions.

[0121] The preferred embodiments of the present invention have been described in detail above. It should be understood that those skilled in the art can make numerous modifications and variations based on the concept of the present invention without creative effort. Therefore, all technical solutions that can be obtained by those skilled in the art based on the concept of the present invention through logical analysis, reasoning, or limited experimentation on the basis of existing technology should be within the scope of protection defined by the claims.

Claims

1. A polymer-reinforced expansive soil swelling inhibitor, wherein the swelling inhibitor comprises component A and component B; the mass ratio of component A to component B is 3-6:1; characterized in that: Component A includes a water-soluble polymer bridging component, a polymer emulsion, a silane hydrophobic component, an antifoaming agent, and a preservative; Component B includes a polyvalent metal salt and a dispersing stabilizer.

2. The polymer-reinforced expansive soil swelling inhibitor as described in claim 1, characterized in that: The water-soluble polymer bridging component includes at least two of lignin sulfonate, carboxymethyl cellulose salt, and polyacrylate.

3. The polymer-reinforced expansive soil swelling inhibitor as described in claim 1, characterized in that: The polymer emulsion is one or more of the following: ethylene-vinyl acetate copolymer emulsion, acrylate emulsion, styrene-acrylic emulsion, and silicone-acrylic emulsion.

4. The polymer-reinforced expansive soil swelling inhibitor as described in claim 1, characterized in that: The silane hydrophobic component is an alkyltrialkoxysilane, a silane emulsion, or a combination thereof.

5. The polymer-reinforced expansive soil swelling inhibitor as described in claim 1, characterized in that: The multivalent metal salts include calcium salts and magnesium salts; the calcium salt is one or more of calcium acetate, calcium chloride, and calcium nitrate, and the magnesium salt is one or more of magnesium chloride, magnesium sulfate, and magnesium acetate.

6. The polymer-reinforced expansive soil swelling inhibitor as described in claim 1, characterized in that: The dispersing stabilizer is one or more of sodium gluconate, sodium citrate, and sodium tartrate.

7. The polymer-reinforced expansive soil swelling inhibitor as described in claim 1, characterized in that: The mass ratio of component A to component B is 4:

1.

8. The polymer-reinforced expansive soil swelling inhibitor as described in claim 1, characterized in that: Component A, by weight, comprises: 40-70 parts deionized water, 8-18 parts lignin sulfonate, 0.5-5 parts carboxymethyl cellulose salt, 1-8 parts polyacrylate, 8-25 parts polymer emulsion, 0.5-5 parts silane hydrophobic component, 0.05-0.5 parts defoamer, and 0.02-0.3 parts preservative.

9. The polymer-reinforced expansive soil swelling inhibitor as described in claim 1, characterized in that: Component B, by mass, comprises: 40-70 parts deionized water, 20-40 parts calcium salt, 8-20 parts magnesium salt, and 1-5 parts dispersant stabilizer.

10. The method for preparing the polymer-reinforced expansive soil swelling inhibitor according to any one of claims 1-9, comprising the following steps: 1) After heating deionized water, add water-soluble polymer bridging components, stir to dissolve, and obtain polymer bridging solution; 2) Add polymer emulsion, silane hydrophobic component, defoamer and preservative to the polymer bridging liquid obtained in step 1), stir evenly to obtain component A; 3) Add the polyvalent metal salt and dispersant stabilizer to deionized water, stir to dissolve, and obtain component B; 4) Filter and seal components A and B separately to obtain a polymer-reinforced expansive soil swelling inhibitor composed of components A and B.

Citation Information

Patent Citations

  • Improved expansive soil as well as preparation method and application thereof

    CN119638276A

  • Expansive soil composite modifier as well as preparation method and application thereof

    CN121379597A

  • Improved expansive soil based on synergistic effect of marble waste powder and xanthan gum and preparation method thereof

    CN121470848A